Regulation of Arabidopsis root development by small signaling peptides - Delay, Christina; Imin, Nijat; Djordjevic, Michael A. (Frontiers in Plant Science, 2013)
Plant root systems arise de novo from a single embryonic root. Complex and highly coordinated developmental networks are required to ensure the formation of lateral organs maximises plant fitness. The Arabidopsis root is well suited to dissection of regulatory and developmental networks due to its highly ordered, predictable structure. A myriad of regulatory signalling networks control the development of plant roots, from the classical hormones such as auxin and cytokinin to short-range positional signalling molecules that relay information between neighbouring cells. Small signaling peptides are a growing class of regulatory molecules involved in many aspects of root development including meristem maintenance, the gravitropic response, lateral root development and vascular formation. Here, recent findings on the roles of regulatory peptides in these aspects of root development are discussed.